2021
DOI: 10.3390/ijms22073503
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Connexin Hemichannel Activation in Disease

Abstract: Gap junctions and connexin hemichannels mediate intercellular and extracellular communication, respectively. While gap junctions are seen as the “good guys” by controlling homeostasis, connexin hemichannels are considered as the “bad guys”, as their activation is associated with the onset and dissemination of disease. Open connexin hemichannels indeed mediate the transport of messengers between the cytosol and extracellular environment and, by doing so, fuel inflammation and cell death in a plethora of disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 94 publications
(164 reference statements)
0
31
0
Order By: Relevance
“…Hemichannels regulate extracellular communications, especially allowing the dissemination of disease. Cx43 is also involved in various signalling transduction pathways that interact individually with intracellular proteins [ 1 , 2 , 3 , 18 , 19 ]. Cx43 can undergo some posttranslational modifications, including phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hemichannels regulate extracellular communications, especially allowing the dissemination of disease. Cx43 is also involved in various signalling transduction pathways that interact individually with intracellular proteins [ 1 , 2 , 3 , 18 , 19 ]. Cx43 can undergo some posttranslational modifications, including phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that a decreased Cx43 phosphorylation at serine 368 increases arrhythmia occurrence in cultured cardiac myocytes and in vivo in animal models. However, the outcome of Cx43 phosphorylation depends on the type of the kinase, the cell target, and the cellular context [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With evidence that Cx43 hemichannel mediated communication contributes to the pathogenesis and progression of tissue damage in secondary complications of diabetes [ 49 , 107 , 108 ], drugs that target Cx43 hemichannels have been identified as potential anti-inflammatory therapies [ 109 , 110 ]. Compounds of interest include Peptide 5, known to bind to the second extracellular loop of Cx43 [ 111 ]; Gap26, which mimics the first extracellular loop of Cx43 [ 112 ]; and αCT1, a Cx43-based peptide [ 113 ].…”
Section: Cx43 Hemichannel Blockers and Treatment Of Inflammation In Diabetes And Its Secondary Complicationsmentioning
confidence: 99%
“…The effects of connexins, the activity of which is under the direct control of external Ca 2+ [ 17 , 18 ], have not been practically investigated for WAT. Global calcium dynamics regulates key intracellular processes in healthy adipose tissue—differentiation, lipid accumulation and insulin signaling [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%